Bowen's Disease on the Left Fifth Finger Successfully Treated with Photodynamic Therapy: A Case Report. Issue 1 (March 2022) - Wu, Wei-Hong; Al-Muriesh, Maher; Deng, Xiao-Hong; Huang, Chang-Zheng
Abstract: Introduction: Bowen's disease is a squamous cell carcinoma in situ. It is more common on the head and neck, less common on the nail units in which it usually involves the second to fourth fingers of both hands. Here, we report a case of Bowen's disease involving the left fifth finger of a 78-year-old Chinese woman. Case presentation: The patient was treated with nine sessions of topical 5-aminolevulinic acid-photodynamic therapy (5-ALA-PDT), with a one-week interval between sessions. The 5-ALA cream was applied to the lesion and the region surrounding its marginal diameter by 0.5cm. After 3-4hours, the lesion was irradiated with 635 ± 10nm red light at an intensity of 80mw/cm 2 for 20minutes. An excellent result with a topical 5-ALA-PDT was reached. Discussion: PDT involves the application of a combination of a photosensitizing drug and light to cause selective damage to the target tissue. PDT is more appropriate than surgical excision for lesions located in sites with poor healing ability. Conclusion: PDT appears to be effective, safe and has a better cosmetic outcome in the treatment of Bowen's disease of the finger unit.